Deciphering the formation period and geological implications of shale tectonic fractures: a mini review and forward-looking perspectives - Li, Hu (Frontiers in Energy Research, 2023)
In complex geological areas, the chronology of tectonic fracture formation is pivotal for the conservation and enhancement of shale gas reservoirs. These fractures, evolving over different geologic epochs, critically influence the modifications in hydraulic fracturing. The review sheds light on an integrated methodology that bridges conventional geological evaluations with experimental diagnostics to decipher the intricate evolution of such fractures in complex geological areas. Shale tectonic fractures, predominantly shear-induced, are delineated into four distinct levels (I, II, III, IV) based on observational scales. Understanding the geometric interplay across these scales provides insight into fracture distribution. Recognizing the constraints of isolated approaches, this study amalgamates macroscopic geological assessments, such as structural evolution and fault analysis, with microscopic techniques, including fluid inclusion studies, isotopic testing, rock AE experiments (U-Th)/He thermochronology, and AFT analysis, etc. This combined approach aids in accurately determining the tectonic fracture’s genesis and its geological time. Future research endeavors should refine this framework, with an emphasis on enhanced geochemical profiling of fracture fillings.